Impact of RNA-Guided Technologies for Target Identification and Deconvolution. (December 2014) - Fennell, Myles; Xiang, Qing; Hwang, Alexia; Chen, Chong; Huang, Chun-Hao; Chen, Chi-Chao; Pelossof, Raphael; Garippa, Ralph J.
For well over a decade, RNA interference (RNAi) has provided a powerful tool for investigators to query specific gene targets in an easily modulated loss-of-function setting, both in vitro and in vivo. Hundreds of publications have demonstrated the utility of RNAi in arrayed and pooled-based formats, in a wide variety of cell-based systems, including clonal, stem, transformed, and primary cells. Over the years, there have been significant improvements in the design of target-specific small-interfering RNA (siRNA) and short-hairpin RNA (shRNA), expression vectors, methods for mitigating off-target effects, and accurately interpreting screening results. Recent developments in RNAi technology include the Sensor assay, high-efficiency miR-E shRNAs, improved shRNA virus production with Pasha (DRGC8) knockdown, and assessment of RNAi off-target effects by using the C9-11 method. An exciting addition to the arsenal of RNA-mediated gene modulation is the clustered regularly interspaced short palindromic repeats/Cas9 (CRISPR/Cas) system for genomic editing, allowing for gene functional knockout rather than knockdown.